(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2015)
This paper deals with hedging which is one of the trading techniques in the futures markets and with the role of hedging as a protecting strategy. Indirectly, hedging affects the competitiveness of a company by reducing overall operating expenses and increasing the level of competitiveness at the same time. The theoretical fundamentals of the hedging strategy are explained, followed by a survey on relevant theoretical findings and research on hedging and its importance in contemporary economic life. Basic types of risk in firms are clearly described, as well as principal hedging models which are in accordance with the International Financial Reporting Standards. Finally, the paper deals with the financial aspects of hedging, stressing the role and the importance of the principle of the financial leverage. Keywords: Hedging, protection, risk, cash flow, efficiency